2020
DOI: 10.14218/jcth.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

NAFLD Epidemiology, Emerging Pharmacotherapy, Liver Transplantation Implications and the Trends in the United States

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a hepatic manifestation of metabolic syndrome. The spread of obesity worldwide in pandemic proportions has led to a rapid rise of NAFLD in developed and developing countries alike. There are no approved pharmacological agents to treat steatohepatitis or advanced fibrosis but obeticholic acid recently has shown some promise in phase III trial. Currently, NAFLD is the number one etiology for simultaneous liver and kidney transplantation in the USA, second most common i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 56 publications
0
40
0
Order By: Relevance
“…Currently, NAFLD already represents one of the most common conditions leading to liver transplantation in many developed countries. 4 5 Due to its initially asymptomatic course, NAFLD tends to be underdiagnosed. Patients are usually diagnosed at advanced stages and specific therapies by specialists are often initiated late.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, NAFLD already represents one of the most common conditions leading to liver transplantation in many developed countries. 4 5 Due to its initially asymptomatic course, NAFLD tends to be underdiagnosed. Patients are usually diagnosed at advanced stages and specific therapies by specialists are often initiated late.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis and alcohol abuse were previously considered the leading risk factors for HCC, but at present, nonalcoholic fatty liver disease (NAFLD) is considered an increasing risk factor. 3 , 4 NAFLD represents a spectrum of liver pathologies that are strongly associated with metabolic disorder. 5 Metabolic dysregulation also contributes to the progression from NAFLD to HCC.…”
Section: Introductionmentioning
confidence: 99%
“…While NASH is the second leading indication for liver transplantation (LT), it is expected that NASH will overtake hepatitis C virus (HCV) as the leading cause, given the efficacy of direct-acting antiviral therapy[ 3 ]. A recent epidemiological study has already confirmed a downward trend for HCV-related LT in the United States[ 4 ].…”
Section: Introductionmentioning
confidence: 99%